Power harvesting using dual transformations of piezoelectricity and magnetism: a review - Awal, M. R. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper discusses the recent progress in micromachined energy harvesting for low power applications. Especially, the combination of piezoelectric and magnetic energy harvesting technologies are focused here. From the review, it is evident that, using the combined platform of piezo and magnetic device is more beneficial compared to the standalone system. It is found that, the proposed combined platform can achieve the output ranged from 40.8μW to 176μW based on the given load mass. Most of the cases it is proven that, the outcome of the hybrid harvester is superior than that of the standalone ones.